Analysis of The Effectiveness of Cultivating Melon (Cucumis melo L.) on Hydroponic Cultivation Methods and Conventional Drip Irrigation Semi-Closed Systems - Muspiah, Aida; Julisaniah , Nur Indah; Farista, Baiq; Sukenti, Kurniasih; Amrulloh, Riyan; Suci, Sukma Irma (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Food problems are a very serious topic globally. This does not only include basic food ingredients such as grains, tubers or other substitute ingredients, but also includes the need for supporting ingredients such as fruit. One of the fruit commodities that many people need is melon (Cucumis melo L.). The availability of melons on the market is currently dominated by farmers' seasonal crops, so their availability is relatively limited outside the season and a surplus during the season, so this has an impact on price stability, both for farmers and consumers. One method that can be offered for this problem is how to carry out cultivation that is not tied to the season by using a greenhouse combined with hydroponic or conventional drip irrigation cultivation methods. The results show that the use of hydroponic methods and drip irrigation can stimulate the growth and especially the development of melon plants. The appearance of flowers in the hydroponic system starts at 2-3 WAP, while in the drip irrigation system it starts at 3-4 WAP. The emergence of productive branches in both methods also takes place from the age of 2 WAP and continues to grow. So from several aspects such as optimal growth, long-term cost efficiency, sustainable agriculture and efficient use of water for agriculture, these two methods can be an effective alternative for melon cultivation.